2018
DOI: 10.29080/biotropic.2017.1.1.17-22
|View full text |Cite
|
Sign up to set email alerts
|

Deteksi Fragmen DNA Rendah Pengkode Gen Sitokrom B (cyt b) Babi pada Sampel Mie Instan Menggunakan Metode Polymerase Chain Reaction (PCR)

Abstract: Mie instan merupakan makanan yang sangat digemari oleh masayarakat Indonesia, selain cara penyajiannya yang cepat dan harganya terjangkau, rasa dari mie instan juga tidak kalah dengan makanan lainnya. Baru-baru ini sedang marak produk mie instan yang di impor dari Korea dan saat ini sedang digandrungi para remaja di Indonesia. Produk tersebut diduga mengandung babi, dugaan tersebut kemudian ditindak lanjuti oleh Badan Pengawas Obat dan Makanan selaku instansi yang berwenang untuk melakukan pengawasan terhadap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The case of halalness food product that occurred in Indonesia is a public unrest that is often faced with uncertainty and threatened to consume food products that are not halal because of ignorance that the food they consume turns out to contain a mixture of ingredients that are forbidden in Islam or even from other reviews there are some the stages that cause food to become haram. Winarsih et al (2017) reported the contamination of pork in instant noodle in Surabaya. Fibriana et al (2012) reported contamination of pork found in meatball snacks in Salatiga.…”
Section: Introductionmentioning
confidence: 99%
“…The case of halalness food product that occurred in Indonesia is a public unrest that is often faced with uncertainty and threatened to consume food products that are not halal because of ignorance that the food they consume turns out to contain a mixture of ingredients that are forbidden in Islam or even from other reviews there are some the stages that cause food to become haram. Winarsih et al (2017) reported the contamination of pork in instant noodle in Surabaya. Fibriana et al (2012) reported contamination of pork found in meatball snacks in Salatiga.…”
Section: Introductionmentioning
confidence: 99%